Deletion of the Pemt gene increases progenitor cell mitosis, DNA and protein methylation and decreases calretinin expression in embryonic day 17 mouse hippocampus - Zhu, Xiaonan; Mar, Mei-Heng; Song, Jiannan; Zeisel, Steven H (Brain research. Developmental brain research, 2004)
Choline is a required nutrient and is derived from the diet as well as from de novo synthesis catalyzed by phosphatidylethanolamine N-methyltransferase (PEMT). We previously reported that choline availability during pregnancy alters mitosis and neuronal protein expression during fetal brain development in wild-type mice and rats, and that Pemt−/− mice become choline deficient. In this study, we examined brain development in these knockout mice. Pregnant Pemt−/− and wild-type mice were fed AIN-76A diet until gestation day 17 (E17) when the fetal brains were harvested. Phosphorylation of histone H3 (a measure of mitosis) and calretinin (a GABAergic neuronal marker) were assessed in hippocampal regions. We observed increased numbers of phosphorylated histone H3 positive cells in the Pemt−/− mice (up 54% compared to wild-type mice; p<0.01). We also found decreased calretinin labeling in Pemt−/− (down to 43% compared to wild-type mice; p<0.01). Thus, there was increased stem cell proliferation in the neuroepithelium and decreased GABAergic neuronal differentiation of these animals on E17. These results are opposite to what would have been expected in choline-deficient mice. The concentrations of S-adenosylmethionine (up 21%; p<0.05) and methylation of DNA (up 46%) and proteins (up 12%; p<0.01) in hippocampus were significantly increased in Pemt−/− mice, suggesting that increased S-adenosylmethionine availability may mediate the observed developmental changes. This is the first report of altered brain development in Pemt−/− mice.